2001
DOI: 10.2214/ajr.176.1.1760119
|View full text |Cite
|
Sign up to set email alerts
|

Incompetent and Dilated Ovarian Veins

Abstract: Incompetent and dilated ovarian veins are frequently seen on CT in asymptomatic parous women. As an isolated finding, it is unlikely to be associated with pelvic congestion syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(19 citation statements)
references
References 10 publications
0
15
1
3
Order By: Relevance
“…Prevalence of PVI in the left OV was variously reported at 10%, 17%, 18%, 38% and 47%. 70,[82][83][84]87 The varying thresholds for defining OV dilatation may give rise to these differences, as might the imaging systems deployed, although no apparent association can be deduced here. CT may overmagnify vessel diameters by 20% yet be unable to detect small veins, and some distention of the OV may occur as a result of the increased intra-abdominal pressure caused by breath holding.…”
Section: A Review Of the Association Between Pelvic Vein Incompetencementioning
confidence: 84%
See 1 more Smart Citation
“…Prevalence of PVI in the left OV was variously reported at 10%, 17%, 18%, 38% and 47%. 70,[82][83][84]87 The varying thresholds for defining OV dilatation may give rise to these differences, as might the imaging systems deployed, although no apparent association can be deduced here. CT may overmagnify vessel diameters by 20% yet be unable to detect small veins, and some distention of the OV may occur as a result of the increased intra-abdominal pressure caused by breath holding.…”
Section: A Review Of the Association Between Pelvic Vein Incompetencementioning
confidence: 84%
“…A retrospective study of the preoperative helical CT scans of female kidney donors provides data on the incidence of OV varices and incompetence in an asymptomatic population. 82 An OV diameter of > 7 mm was considered to be dilated, whilst reflux was complete opacification during the arterial phase of CT angiography; this latter observation defined incompetence. Medical note review implied that no women reported pelvic or abdominal pain, although 4 out of 34 had small fibroids.…”
Section: Prevalence Of Pelvic Vein Incompetence In Asymptomatic Populmentioning
confidence: 99%
“…Selective venography has been considered the gold standard for demonstrating pelvic incompetence as it can potentially show communication between incompetent pelvic veins (ovarian and/or internal iliac) and lower limb varicosities, but a recent study cautions reliance on this modality [ 71 ]. However, as dilated and presumed incompetent veins have been described in asymptomatic parous women [ 2 ], a more functional assessment of pelvic venous incompetence may be required and transvaginal, transperineal or transrectal duplex sonography have been suggested to be such an investigation [ 5 , 6 ]. Pre-operative assessment with functional imaging techniques not involving ionizing radiation such as ultrasound or MR venography in an ‘upright scanner’, is desirable and such techniques may be reproducible with appropriate training.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian and other pelvic varices (such as in the distribution of the internal iliac veins) are not an infrequent finding in adult women, and particularly those who have previously had at least one pregnancy associated with a vaginal delivery or at least a significant trial of labour [ 1 ]. However, they are also well described in asymptomatic parous women [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multi-detector computed tomography (MDCT) has been established as a rapid, non-invasive technique for evaluating anatomy and diseases of the pelvic region in women [Bazot et al, 1999; Foshager & Walsh, 1994; Kumar et al, 2002; MacSweeney & King, 1994; Occhipinti et al, 1993; Rigsby & Siegel, 1994; Rozenblit et al, 2001; Saksouk & Johnson, 2004]. Multi-detector CT uses x-rays, an array of multiple detectors, and advanced computer processing to generate high-detail slice images of the body [Horton et al, 2002].…”
Section: Introductionmentioning
confidence: 99%